PEMBERDAYAAN PERPUSTAKAAN PESANTREN BERBASIS OTOMASI DAN DIGITAL - Muhammad Amir Mahmud (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2013)
Library is one means a place to get information.Today many libraries are still not maximized utilization. This is due to several factors, including the old paradigm that sees the library just as